Ethics, Emotions, and the Skills of Talking About Progressing Disease With Terminally Ill Adolescents: A Review - Rosenberg, Abby R. (JAMA Pediatr, 2016)
IMPORTANCE: For clinicians caring for adolescent patients living with progressive, life-threatening illness, discussions regarding prognosis, goals of care, and treatment options can be extremely challenging. While clinicians should respect and help to facilitate adolescents’ emerging autonomy, they often must also work with parents’ wishes to protect patients from the emotional distress of hearing bad news. OBSERVATIONS: We reviewed the ethical justifications for and against truth-telling, and we considered the published ethical and practice guidance, as well as the perspectives of patients, parents, and clinicians involved in these cases. We also explored particular challenges with respect to the cultural context, timing, and content of conversations at the end of adolescents’ lives. In most cases, clinicians should gently but persistently engage adolescents directly in conversations about their disease prognosis and corresponding hopes, worries, and goals. These conversations need to occur multiple times, allowing significant time in each discussion for exploration of patient and family values. While truth-telling does not cause the types of harm that parents and clinicians may fear, discussing this kind of difficult news is almost always emotionally distressing. We suggest some “phrases that help” when clinicians strive to deepen understanding and facilitate difficult conversations with adolescents, parents, and other family members. CONCLUSIONS AND RELEVANCE: The pediatrician’s opportunities to engage in difficult conversations about poor prognosis may be rare, but such conversations can be crucial. These discussions affect how patients live at the end of their lives, how they die, and how their families go on. Improved understanding of basic principles of communication, as well as augmented understanding of patient, family, and clinician perspectives may better enable us to navigate these important conversations.